Algorithmic Decision Theory First International Conference, ADT 2009, Venice, Italy, October 2009, Proceedings - Rossi, Francesca; Tsoukias, Alexis (Lecture Notes in Artificial Intelligence, 2009)
This volume contains the papers presented at ADT 2009, the first International Conference on Algorithmic Decision Theory. The conference was held in San Servolo, a small island of the Venice lagoon, during October 20-23, 2009. The program of the conference included oral presentations, posters, invited talks, and tutorials. The conference received 65 submissions of which 39 papers were accepted (9 papers were posters). The topics of these papers range from computational social choice preference modeling, from uncertainty to preference learning, from multi-criteria decision making to game theory.